MODELING THE PROCESS OF FORMING THE SKILLS AND PEDAGOGICAL ANALYSIS OF MUSICAL WORKS OF FUTURE MUSIC TEACHERS - Mozgalova, Nataliia; Novosadova, Anna; Novosadov, Yaroslav; Seleznev, Serhii; Kshivak, Yuriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The article highlights the importance of the skills of artistic and pedagogical analysis of musical works for the success of piano training of music teachers. The purpose of the article is to analyze the process of modeling the skills of artistic and pedagogical analysis of musical works of future music teachers. The research used a set of methods: theoretical (analysis of scientific literature, theoretical modeling, comparison, generalization), empirical (observation, questionnaires, testing), methods of processing experimental data for the purpose of quantitative and qualitative analysis of diagnostic results. The content of the concepts: «skill», «skill of artistic-pedagogical analysis of musical works» is clarified, the purpose, task, essence, features and functions of artistic-pedagogical analysis are defined. A model of the formation of the skills of artistic and pedagogical analysis of musical works in the process of piano training has been developed, pedagogical conditions, principles and stages (cognitive-informational, value-orientational, independent-creative) of its implementation have been substantiated. The results of the empirical study showed that in the process of piano training of music teachers, the artistic and pedagogical analysis is not sufficiently updated. At individual lessons in the piano class, only its individual elements are used: biographical information, stylistic features and analogies, analysis of means of expression. Innovative technologies and methods (motivational, cognitive, interactive) of forming skills of artistic and pedagogical analysis are proposed. It has been proven that artistic and pedagogical analysis is a powerful and effective means of developing social skills (soft skills), as it allows students to be involved in various types of musical activities: artistic-cognitive, artistic-analytical, artistic-performing. The conducted research confirmed the relevance of artistic and pedagogical analysis in the process of piano training of music teachers.